Napolean's military Maxism - Cairnes ,William Elliot 1862-1902; D'Aguilarm George C (Dover Publications, 2004)
This classic brings together a rich sampling of the knowledge and wisdom of one of history's greatest military commanders. The concise text not only provides a fascinating glimpse of the French leader's intellectual ability for conducting military operations but also reveals his thoughts, theories, and commentaries on waging war and the art of conducting statecraft